Examining students' perspectives on the use of artificial intelligence tools in higher education: A case study on AI tools of graphic design - Ahmed Alsswey (Acta Psychologica)
Understanding and utilizing AI tools ensure that designers, particularly students, remain involved in a rapidly evolving industry. This study aimed to investigate students' perspectives on the use of AI tools in graphic design. A pre–post-test control group design was used, involving 112 students (56 in the intervention group and 56 in the control group) from Al-Zaytoonah University of Jordan who were enrolled in the design software course. The findings revealed significant differences between the intervention and control groups regarding Utilitarian Benefits, Hedonic Benefits, Learnability, and User Experience, with students in the intervention group showing greater improvements in these areas. Based on these results, the study recommends incorporating AI design tools into the educational curriculum as an effective learning method and strategy for students.